Design of Reactor for The Production of Sodium Thiosulfate (Na2S2O3) Crystal - Chairul Islam, Sultan Nazmi (Universitas Mulawarman, 2024)
In this research, the design and analysis of a batch reactor for the production of Sodium Thiosulfate crystal was carried out. This research was carried out with computational analysis and calculations of the reactor, stirrer and mass balance using the Microsoft Excel application. It is hoped that the manufacture of Sodium Thiosulfate can be scaled up on a factory scale so that a place is needed to react the raw materials from which the Sodium Thiosulfate is made. The specifications for sodium thiosulfate production at an industrial scale (1000 times larger than the lab scale) require a volume of 186.1300 ft3, a height of 2.8147 ft, and one stirrer with a power of 1800 Hp, based on calculations from the batch reactor and stirrer. The calculations were performed using Microsoft Excel without considering effectiveness factors. The calculation results indicate that the reactor's design and performance analysis are applicable.